Forestry Education and Training in India - Malhotra, P. P. (Indian Forester, 1986)
In the present paper a historical background of development of forestry education and training in India has been described right from its beginning in the day. Of Dr. Dietrich Brandis till todday. The puny seedling implanted by Dr. Dietrich Brandis in 1878, with the name of "Central Forest School" at Dehra Dun, has grown into a gigantic tree with as many as thirteen Forest Colleges in the country. The paper gives a broad outline of the Forestry Training Institutions io India and the personnel trained at various levels.